Istanbul Merchant Association - Sever, Murat (Journal of Applied And Theoretical Social Sciences, 2020)
The Istanbul Merchant Association was an effective institution of the trade capital of its time. It set up various commissions, printed the Turkey Economic Journal. It has pioneered the organization of the first civil society congress on the economy named 1948 Turkey Economic Congress. It is among the most important non-governmental organizations in the field of Economic History in Turkey during the Republican Era. These activities and the power to influence public opinion in Turkey show similarities with TUSIAD of the present time which holds an important place in the business world. In this study, in the light of the developments of the period, the establishment process of the Association, the reason and aims of its establishment, and its member structure are discussed. In addition, the ideas of Ahmet Hamdi Başar, the founding father, board member and general secretary of the Association, are mentioned in places and discussions on etatism and liberalism of the period are mentioned.